Perbandingan Kadar Emisi Gas Buang Karbon Monoksida (CO) Pada Kendaraan Bermotor Sistem Injeksi Otomatis - Evi Susilawati; Zulfikar Ali As; Munawar Raharja (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2018)
The Comparison Of Emission Levels Of Carbon Monoxide Exhaust Gas In Automatic Motor Vehicle Injection System. Transportation plays a very big role as a source of air pollution, especially exhaust emissions reach 60-70%. CO emitted by motor vehicle which exceed the standard be able to cause disturbance and even death. The development of a two-stroke engine vehicle into a four-step engine is a people demand who want a vehicle which is easy and comfortable. Indonesia has many different types of vehicles, but two types of motor vehicles with the YMJET-FI and PGM-FI system are most on the market. Three fuels such as premium, pertalite and pertamax are used by the public. This research was observational analytic, using Posttest Only Design to analyze the CO emission from YMJET-FI and PGM-FI engine with premium fuel, pertalite and pertamax. CO emission was tested at engine speed of 1.900-2.000 rpm and temperature 80oC. Analysis used Two Way Analysis of Variance statistic test with α = 0,05%. The results showed that YMJET FI using premium emitted CO as 0,23%, pertalite 0,32% and pertamax 0,37%. PGM-FI using premium emitted 0,21% , pertalite 0,24% and pertamax 0,25%. The conclussion is, both of YMJET-FI and PGM-FI, using premium, pertalite and pertamax emitted CO lower than the emission quality standard according to KemenLH 2009 such as of 4,5%.